A multigene circulating biomarker to predict the lack of FOLFIRINOX response after a single cycle in patients with pancreatic ductal adenocarcinoma. (March 2023) - van Eijck, Casper W.F.; de Koning, Willem; van der Sijde, Fleur; Moskie, Miranda; Groot Koerkamp, Bas; Homs, Marjolein Y.V.; van der Burg, Sjoerd H.; van Eijck, Casper H.J.; Mustafa, Dana A.M.
Abstract: Introduction: 5-fluorouracil, folinic acid, irinotecan and oxaliplatin (FOLFIRINOX) is promising in treating patients with pancreatic ductal adenocarcinoma. However, many patients and physicians are reluctant to start FOLFIRINOX due to its high toxicity and limited clinical response rates. In this study, we investigated the effect of a single FOLFIRINOX cycle, in combination with a granulocyte colony-stimulating factor, on the blood immune transcriptome of patients with pancreatic ductal adenocarcinoma. We aimed to identify an early circulating biomarker to predict the lack of FOLFIRINOX response. Methods: Blood samples of 68 patients from all disease stages, who received at least four FOLFIRINOX cycles, were collected at baseline and after the first cycle. The response to treatment was radiologically evaluated following the Response Evaluation Criteria in Solid Tumours criteria 1.1. Targeted immune-gene expression profiling (GEP) was performed using NanoString technologies. To predict the lack of FOLFIRINOX response, we developed a FOLFIRINOX delta GEP (FFX-ΔGEP) score. Results: A single FOLFIRINOX cycle significantly altered 395 genes, correlating to 30 significant alterations in relative immune cell abundances and pathway activities. The eight-gene ( BID, FOXP3, KIR3DL1, MAF, PDGFRB, RRAD, SIGLEC1 and TGFB2) FFX-ΔGEP score predicted the lack of FOLFIRINOX response with a leave-one-out cross-validated area under the curve (95% confidence interval) of 0.87 (0.60–0.98), thereby outperforming the predictiveness of absolute and proportional Δcarbohydrate antigen19-9 values. Conclusions: A single FOLFIRINOX cycle, combined with granulocyte colony-stimulating factor, alters the peripheral immune transcriptome indisputably. Our novel FFX-ΔGEP is, to our knowledge, the first multigene early circulating biomarker that predicts the lack of FOLFIRINOX response after one cycle. Validation in a larger independent patient cohort is crucial before clinical implementation. Highlights: The peripheral immune transcriptome is similar among 'pancreatic ductal adenocarcinoma's disease stages. One 5-fluorouracil, folinic acid, irinotecan and oxaliplatin (FOLFIRINOX) cycle is sufficient to alter the peripheral immune transcriptome. Various IC regulatory genes are altered by a single FOLFIRINOX cycle. An eight-gene expression profiling score could predict lack of FOLFIRINOX response.